2023
DOI: 10.1021/acsami.3c05262
|View full text |Cite
|
Sign up to set email alerts
|

Electro-oxidation Reaction of Methanol over Reducible Ce1–xyNixSryO2−δ: A Mechanistic Probe of Participation of Lattice Oxygen

Abstract: Methanol oxidation reaction crucially depends on the formation of −OOH species over the catalyst’s surface. Ni-based catalysts are by far the choice of materials, where the redox couple of Ni2+/Ni3+ facilitates the formation of −OOH species by surface reconstructions. However, it is challenging to oxidize Ni2+ as it generates charge-transfer orbitals near the Fermi energy level. One possible solution is to substitute Ni2+ with a reducible oxide support, which will not only facilitate the Ni2+ → Ni3+ oxidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…It should be noted that the MOR activity was also significantly better than our earlier reports (Figure S7). With optimum doping of Zr in Ce 0.6 Zr 0.35 Ni 0.05 O 2−δ , the current density was found to be highest with 13.12 mA cm –2 . The current density was reduced with further doping of Zr in Ce 0.4 Zr 0.55 Ni 0.05 O 2−δ (9.04 mA cm –2 ).…”
Section: Resultsmentioning
confidence: 97%
“…It should be noted that the MOR activity was also significantly better than our earlier reports (Figure S7). With optimum doping of Zr in Ce 0.6 Zr 0.35 Ni 0.05 O 2−δ , the current density was found to be highest with 13.12 mA cm –2 . The current density was reduced with further doping of Zr in Ce 0.4 Zr 0.55 Ni 0.05 O 2−δ (9.04 mA cm –2 ).…”
Section: Resultsmentioning
confidence: 97%
“…Investigation was carried out to examine the influence of electrochemical surface area (ECSA) on the activity of MOR. The ECSA was calculated with the help of chrono-amperometric studies using the Cottrell equation Q = 2 n FAD 1/2 C o t 1/2 π –1/2 , as shown in Figure . In the equation, Q = charge in coulomb, F = Faraday constant, n = number of electrons being transferred, A = area of electrode in cm 2 , D = diffusion coefficient of [K 3 Fe­(CN) 6 ] (7.6 × 10 –6 cm 2 s –1 ), t = time (s), and C o = concentration of K 3 Fe­(CN) 6 in mol cc –1 .…”
Section: Resultsmentioning
confidence: 99%
“…Oxides of nickel (Ni) have emerged as extensively studied transition-metal oxides for electrocatalysis due to their advanced oxygen-ion conductivity, structural diversity, nontoxicity, reduced onset potential, and improved catalytic activity. Research has indicated that the electrocatalytic oxidation of methanol by Ni-based oxides are facilitated by the Ni 3+ /Ni 2+ redox couple, primarily due to the creation of highly active surface-intermediate species known as Ni–OOH. …”
Section: Introductionmentioning
confidence: 99%
“…16,17 We further substituted Ce with Sr (Co 3 O 4 /Ce 1− y Sr y O 2− δ ) to enhance the oxidizing power of CeO 2 as Sr with a lower oxidation potential is a judicious choice for ameliorating the redox behaviour of cerium and cobalt. 18–23 To further enhance the impact of oxygen vacancies, we partially substituted the cobalt sites with another transition metal, namely Cu (Co 3− x Cu x O 4 /Ce 1− y Sr y O 2− δ ). The substitution of cobalt with copper will elevate the oxidation state of cobalt.…”
Section: Introductionmentioning
confidence: 99%